A theory on ICER pricing and optimal levels of cost-effectiveness thresholds: a bargaining approach - Berdud, Mikel; Ferraro, Jimena; Towse, Adrian (Frontiers in Health Services, 2023)
In many health systems around the world, decisions about the reimbursement of—and patient access to—new medicines are based on health technology assessments (HTA) which, in some countries, include the calculation of an incremental cost-effectiveness ratio (ICER). Decision-makers compare the ICER against a pre-specified value for money criterion, known as the cost-effectiveness threshold (CET), to decide in favour of or against reimbursement. We developed a general model of pharmaceutical markets to analyse the relationship between the CET value and the distribution of the health and economic value of new medicines between consumers (payers) and producers (life science industry developers). We added to the existing literature in three ways: including research and development (R&D) cost for developers as a sunk cost; incorporating bargaining using the Nash bargaining solution to model payer bargaining power from regulation and use of competition; and analysing the impact of a non-uniform distribution of developers R&D costs on the supply of innovation. In some circumstances of bargaining power distribution and R&D cost, we found that using a CET value in HTA decision-making higher than the supply-side CET is socially efficient. Decision-makers should consider adjustable levels of the CET or interpretation of ICERs higher than the CET according to the bargaining power effect. The findings of this research pointed to the need for more research on the impact of bargaining power, how R&D investment responds to rewards, i.e. the elasticity of innovation, and pre- and post-patent expiry modelling.